2019
DOI: 10.1007/978-3-030-11999-7_10
|View full text |Cite
|
Sign up to set email alerts
|

The Cold War in South African History Textbooks

Abstract: A remarkable feature of the Cold War is its coincidence with the period of apartheid in South Africa, in which it played an important role. This is evident in school textbooks, where it is a major topic in the most recent years of history. But while there is a growing body of work on the Cold War in Africa, there is a very small literature on its manifestation in South Africa and, with one exception, nothing on how school textbooks may have reinforced or challenged its main precepts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…He found that all the authors of four textbooks placed the blame on both sides of the conflict. Chisholm and Fig (2019) explain how the prevalent use of the grammatical passive voice in textbooks used in South Africa contributes to constructing the image of Africa and Africans as powerless victims of the great rivalry of the superpowers in their study named "The Cold War in South African History Textbooks". Oteíza and Castro (2019) point out how history textbooks treat the era of Latin American dictatorships and part that the United States played in this phase during the Cold War.…”
Section: The Teaching Of Contemporary History In Turkeymentioning
confidence: 99%
“…He found that all the authors of four textbooks placed the blame on both sides of the conflict. Chisholm and Fig (2019) explain how the prevalent use of the grammatical passive voice in textbooks used in South Africa contributes to constructing the image of Africa and Africans as powerless victims of the great rivalry of the superpowers in their study named "The Cold War in South African History Textbooks". Oteíza and Castro (2019) point out how history textbooks treat the era of Latin American dictatorships and part that the United States played in this phase during the Cold War.…”
Section: The Teaching Of Contemporary History In Turkeymentioning
confidence: 99%